Recent Progress in Distiller’s Grains: Chemical Compositions and Biological Activities - Ran He; Yubo Yang; Yongsu Li; Minghua Yang; Lingyi Kong; Fan Yang (Molecules, 2023)
Distiller’s grains (DGs) are solid mixtures that remain after the production of alcoholic beverages. A large amount of DGs is produced each year during the brewing process. Currently, they are mostly used as a feedstock or substrate in the feed industry. However, the lack of a comprehensive understanding of the chemical composition of DGs is a major constraint on their further development and application for high-value-added usages. Some studies were published on the bioactive constituents of DGs in several different types of journals. Data were therefore collated to provide a comprehensive overview of these natural products. DGs are rich in phenols, phytosterols, and fatty acids, in addition to general lipid and protein constituents. These compounds and their related extracts possess diverse biological activities, including antioxidant, anti-inflammatory, and anti-hyperglycaemic effects. We hope that this review will provide research incentives for the further development and utilisation of DGs to develop high-value-added products.